“It's Like a Drive by Misogyny”: Sexual Violence at UK Music Festivals - Bows, Hannah (Violence against women, 2024)
Despite increasing scholarly and media attention on sexual violence in public spaces, including those associated with the night-time economy and licensed venues, music festivals have been largely absent from research and policy. This paper presents the findings from the first UK study of sexual violence at music festivals, drawing on data from interviews with 13 women who have experienced some form of sexual harassment or assault at a festival. Analysis reveals that sexual violence at festivals occurs on a continuum and represents an extension of rape culture through which sexual violence is culturally condoned and normalized, enabled through a number of environmental and culture features that are unique to festivals.